Late-presenting congenital diaphragmatic hernia with tension gastrothorax: a case series - Mohamed Nahrudin, Khairoon Diyana; Ab. Rahman, Norhafiza; Othman, Mohd Yusran; Abdullah, Mohd Yusof (2022)
Introduction: Congenital diaphragmatic hernia (CDH) is commonly diagnosed during neonatal period, however they may be detected at a later age with various clinical manifestation. We share 3 cases of tension gastrothorax as a manifestation of late-onset CDH.